Evidence for the association of Y-chromosome haplogroups with susceptibility to spermatogenic failure in a Chinese Han population. Issue 4 (21st December 2007) - Yang, Y; Ma, M; Li, L; Zhang, W; Xiao, C; Li, S; Ma, Y; Tao, D; Liu, Y; Lin, L; Zhang, S
Abstract : Introduction: Y chromosomes are genetically highly variable due to frequent structural rearrangements. The variations may create a genetic background for the susceptibility to Y-related spermatogenic impairment, although few data have been accumulated about the possible correlation between the Y-chromosome haplotype and the predisposition of men to spermatogenic failure. Objective: To investigate the possible association of Y-chromosome background with spermatogenic failure. Methods: The distribution of 18 Y-chromosome haplogroups was compared between 414 infertile men with azoospermia or oligozoospermia and 262 normozoospermic men with or without AZFc deletions in a Han population of Southwest China. Results: A significant population difference in Y-haplogroup distribution was found between the groups of normozoospermia and azoospemia or oligozoospermia, and between the patient groups with oligozoospermia and azoospermia without AZFc deletions. Interpopulation comparison of Y haplogroup frequencies showed that the distribution of the haplogroups C, K* and O3* were significantly different between the groups. Conclusion: This study provides evidence for the association of Y-chromosome background with impaired spermatogenesis, suggesting that Y variations play a role in the occurrence and even the severity of spermatogenic failure. Furthermore, both AZFc deletions and other Y-chromosome structural variations may be important for determining the susceptibility to spermatogenic failure. Our findings emphasise the necessity of more extensive study on Y-chromosome variations for better understanding of spermatogenesis and its pathology.